The role of acid phosphatases in the phosphorus nutrition of arctic tundra plants - Kroehler, Carolyn J. (Virginia Polytechnic Institute and State University, 1987)
The acid phosphomonoesterase activity associated with two major rooting strategies in arctic tundra plants was examined: that of Eriophorum vagina tum, a dominant plant in tussock tundra ecosystems, with its predominantly non-mycorrhizal root system; and that of ectomycorrhizal roots. Eriophorum has phosphatase activity which is evenly distributed along its root surface, has a pH optimum at soil pH (3.5-4.0), and continues at substantial rates at 1 °C. Inorganic phosphorus inhibits activity only 7 to 19%. In addition, Eriophorum has phosphatase activity associated with all the "below-ground" components of its tussock growth form: dead roots, leaf sheaths, and soil. Plants with higher tissue phosphorus growing in soils with higher available phosphate in general had higher live and dead root, leaf sheath, and soil phosphatase activity in both natural and manipulated sites of higher plant productivity. Yearly and seasonal variation sometimes exceeded differences among treatments, suggesting that enzyme activity would not provide a reliable measure of plant or soil phosphorus levels. Experiments with radiolabeled inositol hexaphosphate showed that Eriophorum is able to hydrolyze and absorb inorganic phosphate from an organic phosphate source. A comparison of enzyme hydrolysis rates with inorganic phosphate assimilation rates indicates that organic phosphate hydrolysis may occur as rapidly as inorganic phosphate absorption. Inorganic phosphate released by root surface phosphatase activity could satisfy approximately 65% of the annual phosphate demand of Eriophorum. Phosphatases of two ectomycorrhizal fungi (Cenococcum geophilum and Entoloma sericeum) responded similarly to growth in axenic culture at 2 or 50 micromolar KHPO or sodium inositol hexaphosphate: surface Vmax estimates were significantly greater for 2 micromolar- than for 50 micromolar-grown isolates. The presence of constitutive extracellular soluble phosphatase activity resulted in the appearance of inorganic phosphate in media initially supplied only ...